Ross Macdonald, Redivivus? - Robert Lance Snyder (European Journal of American Studies)
Ross Macdonald, the author of eighteen Lew Archer novels in the 1950s through the 1970s, seems to be undergoing a revival of interest. After a definitive biography appeared in 1999, the Library of America, a sure benchmark of literary recognition, released in 2015 the first of three volumes devoted to his fiction; the same year saw the publication of his letters to and from Eudora Welty; and in 2016 Fantagraphics Books issued Macdonald’s marathon interviews with Paul Nelson. During his lifetime this author of detective fiction had both ardent champions and occasional detractors, but an examination of The Doomsters (1958), The Galton Case (1959), The Far Side of the Dollar (1965), and The Goodbye Look (1969) reinforces the judgment of Bernard A. Schopen, a scholar writing four years before Macdonald’s death, that his work “fully deserves evaluation as literature” and “purposeful art,” not least because of his trenchant critique of the American Dream.